World equity premium based risk aversion estimates - Lorenzo C. G. Pozzi; Casper G. de Vries; Jorn Zenhorst (Center for Economic Studies and ifo Institute (CESifo), 2010)
The equity premium puzzle holds that the coefficient of relative risk aversion estimated from the consumption based CAPM under power utility is excessively high. Moreover, estimates in the literature vary considerably across countries. We gauge the uncertainty pertaining to the country risk aversion estimates by means of jackknife resampling and pooling. The confidence band for the world risk aversion estimate from the pooled country data is much tighter and the pooled point estimate presents less of a puzzle than the individual country estimates.
Keywords: E21; G12; 330; equity premium puzzle; jackknife; pooling; Equity Premium Puzzle; Risikoaversion; Capital Asset Pricing Model; Theorie; Schätzung; OECD-Staaten